New paedomorphic brachiopods from the abyssal zone of the north-eastern Pacific Ocean - Bitner, Maria Aleksandra; Melnik, Vjacheslav P.; Zezina, Olga N. (Zootaxa, 2013)
New Recent very small but sexually mature brachiopods have been found at abyssal depths (4580–4850 m) in the Clarion- Clipperton Zone of the Pacific Ocean. They are characterized by simple (under-developed, juvenile) morphological fea-tures, which are interpreted here as paedomorphic, indicating the importance of heterochrony in the evolution of deep-sea brachiopods. We have described these brachiopods as representing two new genera and species, i.e. Oceanithyris juveni-formis Bitner & Zezina (Family ?Dyscoliidae) and Simpliciforma profunda Bitner & Zezina (Superfamily Gwynioidea).